PERUBAHAN WATAK HIDROLOGI SUNGAI-SUNGAI BAGIAN HULU DI JAWA - Nugroho, Sutopo Purwo (Center for Environmental Technology, 2009)
The hydrological character of the rivers in Java has changed. The trend flow of upstream rivers in Java declined. Significance level of the trend decline in the upstream was large enough. This indicates that the basic flow (base flow) from these rivers has been reduced. The cause of the trend decline in river flow is strongly influenced by a combination of the effects of global climate change and the influence of anthropogenic. The influence of climate change is marked by decreasing annual rainfall. While anthropogenic influences include changes in land use, reduced water catchment area, increasing population pressures and settlements. To identify which factors are most influential between the two factors are very difficult to do because of limited data on land use change.Ã‚Â Keywords: discharge, trend, climate change, landuse, anthropogenic